Unlearning Introductions: Problematizing Pedagogies of Inclusion, Diversity, and Experience in the Gender and Women’s Studies Introductory Course - O'Sullivan, Meg Devlin; Bryant, Karl; Hewett, Heather (Atlantis)

(untitled) (Mount Saint Vincent University, 2016)
This article interrogates the ways in which the ideas of diversity, experience, and inclusion became central to the introductory Gender and Women’s Studies (GWS) course at one institution and the way that various stakeholders define and interpret these terms. After providing a short local history and analyzing current and former instructors’ understandings of these concepts as they function in the GWS introductory classroom, the authors further explore these themes with two case studies: transgender inclusion and Native American feminisms.